The most useful and most necessary resources for online teaching - Quevedo Posada, Lucía Michelle; Morales Hernández, Elsa Leonor; Fuentes Rodríguez, Douglas Vladimir (2024)
This document talks about the activities for the development of a teacher in a virtual classroom, like quizzes, games, presentations, etcetera; as well as techniques to keep the students engaged and evaluation systems development. This paper discusses the studied tools and resources that educators have available and that were learned during the specialization Course. This document also talks about the achievements acquired at the end of it as well as how platforms for video conferences were different one from the other and the benefits of each one. At the end students were capable of drawing their own conclusions about which platform, tool, game and application was the best for their teaching needs. Keywords: Platforms ; Videoconference ; Tool ; Sources ; Resources ; On-line.